Pengaruh Motivasi Belajar Terhadap Kemandirian Belajar Peserta Didik SMP Negeri 3 Satap Kabila Bone - Hadji, Sriwulandari; Hafid, Radia; Sudirman, Sudirman; Panigoro, Meyko; Ardiansyah, Ardiansyah; Kasim, Mamang (State University of Gorontalo, 2026)
The purpose of this study was to determine the influence of learning motivation on students' learning independence at SMP Negeri 3 Satap Kabila. This study used a quantitative approach with an ex post facto method. Data collection methods used in this study were observation, documentation, and questionnaires. The sample used in this study was 30 students with a total sampling technique. The results of the study showed that the simple linear regression test resulted in the equation Ý 53.782 +0.586X, with a constant score of 53.782 and a coefficient of 0.586. This indicates that the direction of the influence of variable X on variable Y is positive, and the sig. of 0.000 0.05 means that learning motivation has a positive and significant effect on student learning independence at SMP Negeri 3 Satap Kabila. The regression coefficient of 0.586 indicates that a one-unit increase in learning motivation leads to an increase of 0.586 or 58% in learning independence. The coefficient of determination obtained before was 0.534, meaning that 53.4% of the variability in student learning independence at SMPN 3 Satap Kabila Bone can be explained by the learning motivation variable. Meanwhile, the remaining 46.6% is influenced by other variables not examined in this study.